2018
DOI: 10.1029/2018jc014017
|View full text |Cite
|
Sign up to set email alerts
|

Influences of the Kuroshio on Interisland Remote Connectivity of Corals Across the Nansei Archipelago in the East China Sea

Abstract: For the preservation and protection of coral habitats along the Nansei Archipelago in the East China Sea, a submesoscale eddy‐resolving synoptic ocean model was developed based on the Regional Oceanic Modeling System coupled with a 3‐D Lagrangian particle tracking model. Millions of neutrally buoyant particles representing coral spawn and larvae were released from 19 major islands and one lagoon every spring from 2012 to 2015. The model results were compared to satellite data, in situ observation, and surface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 75 publications
2
20
0
Order By: Relevance
“…Quantitative pathways of coral spawn and larvae dispersal through direct advection by ocean currents and associated dispersal effects were investigated in our previous study, which used the Regional Oceanic Modeling System (ROMS) coupled with a 3-D Lagrangian particle-tracking model to simulate coral spawn and larvae as neutrally buoyant particles. Although the study showed that particles released off the Yaeyama Islands (i.e., the region around the Sekisei Lagoon) may be advected more than 400 km northeast to reach Okinawa Island within a typical pelagic larval duration of 21 days 4 , we were not able to identify specific source areas for the coral spawn and larvae. Therefore, our current study aims to identify major source areas for (1) the interior Sekisei Lagoon, and (2) the entire Kuroshio downstream region, (and hence, for aiding the poleward coral habitat migration) by using 3-D Lagrangian particle-tracking simulations 4 .…”
Section: Introductionmentioning
confidence: 82%
See 4 more Smart Citations
“…Quantitative pathways of coral spawn and larvae dispersal through direct advection by ocean currents and associated dispersal effects were investigated in our previous study, which used the Regional Oceanic Modeling System (ROMS) coupled with a 3-D Lagrangian particle-tracking model to simulate coral spawn and larvae as neutrally buoyant particles. Although the study showed that particles released off the Yaeyama Islands (i.e., the region around the Sekisei Lagoon) may be advected more than 400 km northeast to reach Okinawa Island within a typical pelagic larval duration of 21 days 4 , we were not able to identify specific source areas for the coral spawn and larvae. Therefore, our current study aims to identify major source areas for (1) the interior Sekisei Lagoon, and (2) the entire Kuroshio downstream region, (and hence, for aiding the poleward coral habitat migration) by using 3-D Lagrangian particle-tracking simulations 4 .…”
Section: Introductionmentioning
confidence: 82%
“…Although the study showed that particles released off the Yaeyama Islands (i.e., the region around the Sekisei Lagoon) may be advected more than 400 km northeast to reach Okinawa Island within a typical pelagic larval duration of 21 days 4 , we were not able to identify specific source areas for the coral spawn and larvae. Therefore, our current study aims to identify major source areas for (1) the interior Sekisei Lagoon, and (2) the entire Kuroshio downstream region, (and hence, for aiding the poleward coral habitat migration) by using 3-D Lagrangian particle-tracking simulations 4 .…”
Section: Introductionmentioning
confidence: 82%
See 3 more Smart Citations